Combined modality chemoradiation in elderly oesophageal cancer patients - Sibyl Anderson; Bruce D. Minsky; Manjit S. Bains; Amanda Hummer; David P. Kelsen; David H. Ilson (2007)
We present a single institution experience with 5-FU, mitomycin-C based chemoradiation for the primary treatment of elderly patients with oesophageal cancer. Twenty-five patients with a median age of 77 years (range 66–88) with a diagnosis of stage II–III squamous cell or adenocarcinoma of the oesophagus were treated at Memorial Sloan Kettering from 1996 to 2001 with two cycles of concurrent 5-FU, mitomycin-C and 50.4 Gy. Owing to age and comorbidity, these patients were not considered surgical candidates. The Charlson comorbidity score was used to evaluate patient comorbidity. Nine patients (36%) experienced grade 3–4 haematologic toxicity. Of the 23 patients evaluable for response, 17 patients (68%) had a negative post-treatment endoscopy and CT scan without evidence of progressive disease. Eleven patients (44%) are alive and 10 (40%) remain without evidence of recurrent or progressive oesophageal cancer at a median follow-up of 35 months. The median overall survival was 35 months and 2-year survival 64%. There was no significant difference in overall survival between Charlson score ⩽2 and those with a score ⩾2 (P=0.10). Similar survival was observed for patients with adenocarcinoma or squamous carcinoma. Primary chemoradiation with two cycles of 5-FU, mitomycin-C, and 50.4 Gy in elderly patients is an active regimen with moderate toxicity, despite the advanced age and heavy comorbidity burden of this cohort. Patients with local/regional oesophageal cancer with adequate functional status should not be excluded from potentially curative treatment based on age alone.